The Influence of Discipline, Loyalty and Leadership on Work Productivity in the Secretariat of the Regional People's Representative Council of Selayar Islands District - Yusuf, Muhammad; Nur, Muh. R; Achsanuddin, A. Nur UA; Munsyir, Mulawarman (MultiTech Publisher, 2024)
Raw materials have an important role in a company's production activities. Companies need to control raw material inventory because it affects the smooth production process. The purpose of this research is to find out whether the application of the EOQ method (Economic Order Quantity) can optimize raw material inventory costs at PT. Bumi Sarana Concrete (Kalla Block). The analytical method used is the EOQ method (Economic Order Quantity), total inventory costs, order frequency, safety stock and reorder point (Re Order Point). The results of this study indicate that using the EOQ method (Economic Order Quantity) can optimize raw material inventory costs. This is proven by the savings generated by the EOQ method. The results of the study show that there is a positive and significant influence of discipline, loyalty and leadership on work productivity. This is evidenced by the results of the test carried out by the t test by looking at the significant value of t count of 0.000 < from the significant level (0.000 < 0.05). Based on the results of the t test that has been carried out on the discipline variable (X1) on work productivity (Y) a value of 0.048 < 0.05 is obtained, besides that it is known that the significant value of X1 to Y is 0.250. Based on the results of the t-test that has been carried out on the loyalty variable (X2) on work productivity (Y) the value is 0.039.